THE FINE STRUCTURE OF THE AXON AND GROWTH CONE OF THE DORSAL ROOT NEUROBLAST OF THE RABBIT EMBRYO - Tennyson, Virginia M. (The Rockefeller University Press, 1970)
The centrally directed neurite of the dorsal root neuroblast has been described from the period of its initial entrance into the neural tube until a well-defined dorsal root is formed. Large numbers of microtubules, channels of agranular reticulum, and clusters of ribosomes are found throughout the length of the early axons. The filopodia of the growth cone appear as long thin processes or as broad flanges of cytoplasm having a finely filamentous matrix material and occasionally small ovoid or elongate vesicles. At first the varicosity is a small expansion of cytoplasm, usually containing channels of agranular reticulum and a few other organelles. The widely dilated cisternae of agranular reticulum frequently found within the growth cone probably correspond to the pinocytotic vacuoles seen in neurites in tissue culture. The varicosities enlarge to form bulbous masses of cytoplasm, which may measure up to 5 µ in width and 13 µ in length. They contain channels of agranular reticulum, microtubules, neurofilaments, mitochondria, heterogeneous dense bodies, and a few clusters of ribosomes. Large ovoid mitochondria having ribonucleoprotein particles in their matrix are common. Dense membrane specializations are found at the basal surface of the neuro-epithelial cell close to the area where the early neurites first enter the neural tube.